An educational application to promote gender equality in primary education - Montaner Bueno , Andrés; Fernández Corbalán, Isabel María (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
Gender inequality is a serious problem that affects not only the female population but societies in general, limiting the possibilities of reaching their potential growth and preventing them from becoming truly democratic societies in which there is real equality of rights. This study presents a didactic application aimed at promoting gender equality applied to groups in the fifth year of Primary Education at a public school in the Region of Murcia. For this we have tried, first of all, to specify the concept of gender and the possible negative repercussions that unequal treatment between men and women entails. Subsequently, we defend the approach that the educational system is an ideal means for the adequate formation of gender identities and the integral development of people. As an instrument for our purposes, we propose the use of reading due to its socializing function, especially in children at earlier ages. In the implementation of our didactic proposal we have used an ethnographic methodology with pre-test and post-test to know the evolution of the participants’ thinking and a series of activities related to the reading of Marta Rivera’s book illustrated by Cecilia Varela called “Ellas hicieron historia: mujeres admirables”. Included here are the analysis of the text, the literary gathering and the simulation of interviews and letters to female historical figures. The results obtained are encouraging, since an improvement in awareness regarding behaviors based on gender equality is observed and it is confirmed that this type of activity constitutes a good line of action to continue training students in this value.